Silicon application influences the prokaryotic communities in the rhizosphere of sugarcane genotypes - Leite, Marcos Renan Lima; de Alcantara Neto, Francisco; Dutra, Alexson Filgueiras; Mendes, Lucas William; Antunes, Jadson Emanuel Lopes; Melo, Vania Maria Maciel; Oliveira, Francisca Andrea Silva; Rocha, Sandra Mara Barbosa; Pereira, Arthur Prudêncio de Araujo; Prado, Renato de Mello [UNESP]; Araujo, Ademir Sérgio Ferreira (Elsevier, 2023)
Silicon (Si) is beneficial to sugarcane production and its application in the soil can influence the microbial communities in the rhizosphere of sugarcane. However, it is unclear how the microbial communities in the rhizosphere of different sugarcane genotypes respond to Si application. This study assessed the effect of Si application on the prokaryotic communities in the rhizosphere of three sugarcane genotypes (RB021754, RB036066, RB92579) during the stages of plant cane and ratoon, through the 16S rRNA gene sequencing. The composition of prokaryotic communities varied by comparing genotypes and Si application in both plant cane and ratoon. In the sugarcane plant, the relative abundance of Planctomycetes and Gemmatimonadetes decreased in the rhizosphere of genotype RB021754, while the relative abundance of Proteobacteria increased in the rhizosphere of genotype RB92579 with Si application. Regarding ratoon cane, the relative abundance of Acidobacteria, Thaumarchaeota, and Planctomycetes increased in the rhizosphere of genotypes RB021754, RB036066, and RB92579, respectively, after Si application. At the genus level, Catenulispora, Sphingoaurantiacus, Luteitalea, and Flavisolbacter presented a positive correlation with Si application, while Alloprevotella, Gaiella, Sporomomusa, and Tahibacter presented a negative correlation. Also, there was an enrichment of N-fixers and plant growth-promoter microbes after Si application. This study has shown that Si application affected prokaryotic diversity and changed the abundance of specific microbial groups, which varied according to different genotypes.
Keywords: Microbial ecology; Plant microbe interaction; Saccharum spp.